Existentialism in Four Malaysian Anglophone Writers: K.S. Maniam, Llyod Fernando, Kee Thuan Chye and Salleh Ben Joned - Rajoo, Krishnaweni (2001)
The intention of this research is to highlight existential features in four Malaysian writers in English: K.S. Maniam (Indian), Lloyd Fernando (Eurasian), Kee Thuan Chye (Chinese) and Salleh Ben Joned (Malay). These writers delineate existentialism in their works in radically different levels of intensity and depth. They fall in a receding slope in their portrayal of existentialism from the first writer, Maniam, to Fernando, Kee and lastly, Salleh. Apart from that, the writers also portray existential sub-themes (or recurring themes) in an irregular manner, based on the times they wrote a particular book, their characterisations, plot, and even their own personal disposition. The writers may also portray this philosophy in their works in either a conscious or unconscious manner. Though existential elements are prevalent in the writings of all four writers (the novels of Maniam and Fernando, Kee's dramas and Salleh's newspaper articles and poems), yet, this philosophy seems to be subscribed to and used by these four writers in diverse ways.